Activity of speaking skills of grade V students with the help of a paired storytelling model on the theme of the environment of SDN Tegalasri 4 - Oktaviarini, Nourma; Astutik, Leny Suryaning (Universitas Kanjuruhan Malang, 2024)
The research aims to analyze and describe the implementation of the learning process of speaking skills by using paired storytelling learning model for fifth grade students of SDN Tegalasri 4. The research method used in this research is qualitative research. The subjects in this study were fifth grade students of SDN Tegalasri 4. Data collection techniques used interviews, observation, and documentation. The results of the learning implementation research using the paired storytelling learning model obtained a scoreÂ 84%